ANALISIS STUDI KASUS KELAYAKAN USAHA PENANGKAPAN IKAN: MENGGUNAKAN PUKAT CINCIN DI LAMPULO BANDA ACEH - Hismendi Hismendi; Ery Jayanti (Universitas Jabal Ghafur, 2022)
Analysis to the Fishing Business Feasibility Using Purse Seine in Lampulo Banda Aceh has been done from March to June 2020. The objective of this analysis is to know the fishing business feasibility using purse seine in Lampulo. Survey methods were used on 8 active purse seine boats and the data were collected by interviewing techniques. Data were analyzed by means investment criteria Net Present Value (NPV), Internal Rate Return (IRR), Net Benefit-Cost Ratio (B/C Ratio), Break Even Point (BEP),and Payback Period (PP). The results show that the value of Net Present Value (NPV) ranges between Rp 1.055.432.152 to Rp 1.857.087.678, Internal Rate Return (IRR) ranges between 20,20% to 20,30%, Net Benefit-Cost (B/C Ratio) ranges between 1,96to 2,42, Break Even Point (BEP) ranges betweenRp 474.737.261 to Rp 604.509.983 by the results fish sell 52.137 Kg to 73.077 Kg and Payback Period (PP) ranges between 1 year and 8 mounth to 2 year and 3 mounth. In other word, fishing business by using purse seine in Lampulo is deserve and reasonable and it has a good prospect to be developed.Keywords: Feasibility Analysis, Investment Criteria, Purse Seine